Perfil epidemiológico, clínico e laboratorial de pacientes com nefrite lúpica submetidos a transplante renal - Albuquerque, Bruna Coelho (Universidade de Fortaleza, 2017)
Made available in DSpace on 2019-03-30T00:18:27Z (GMT). No. of bitstreams: 0 Previous issue date: 2017-11-24 === Introduction: Systemic lupus erythematosus (SLE) is an autoimmune, multisystemic disease, characterized by the production of autoantibodies, deposition of immunocomplexes, systemic inflammation, and tissue damage. About 37% to 45% of SLE patients develop lupus nephritis (NL) at some point in the course of the disease. A proportion of 10 to 30% of patients with NL evolve to chronic kidney disease (CKD), within 15 years after diagnosis, even with aggressive treatment. Objective: To analyze the sociodemographic, clinical and laboratory profile of patients with NL undergoing renal transplantation in a public tertiary hospital. To detect the relapse of SLE and the time of survival of the renal graft and the patient. To identify the score of the index of damage through the criteria of Systemic Lupus International Collaborating Clinics (SLICC) in patients with SLE. To compare the renal survival of the patients under study with other Brazilian research with similar clinical profile. Methods: We analyzed all the records of patients submitted to renal transplantation from July 1996 to May 2016 at the General Hospital of Fortaleza (HGF), a reference center in the North Northeast for transplants. Of these, patients with a diagnosis of NL were selected as the cause of terminal CKD (n = 35), which met the criteria of the American College of Rheumatology (ACR). RESULTS: Of a total of 1.861 renal transplantations, 38 (1.8%) of them were performed in 35 patients with LN, 3 of which underwent more than one transplantation. The mean age of the patients in the diagnosis of SLE was 33.0 ± 11.1 years. The majority were female (94.7%) and non-Caucasian (68.4%). 57.9% underwent renal biopsy before transplantation. The mean of the SLICC was 4.7 ± 1.2. Most donors (71.1%) were deceased. The mean time from diagnosis of SLE to renal transplantation was 10.3 ± 6.4 years. The mean pre-transplantation dialysis time was 3.9 ± 3.7 years. The acute rejection rate in the first year was identified in 7.9% of the patients. The graft and patient surges were, respectively, 97.1% and 100% at six months; 84.9% and 96.9%, in the first year, and 73.3% and 92.5%, in the fifth year. 2.6% had recurrence of SLE. Comparing patients who evolved with graft loss and those who maintained good graft function, we observed a higher prevalence of thrombosis (p = 0.017) and antiphospholipid syndrome (p = 0.036) in the first group. Conclusion: The study demonstrated that patients with NL undergoing renal transplantation had a good survival over a 5-year follow-up period and that the presence of thrombosis and antiphospholipid syndrome were important factors for graft loss. Keywords: Kidney transplantation; Lupus nephritis; Systemic lupus erythematosus. === Introdução: O lúpus eritematoso sistêmico (LES) é uma doença autoimune, multissistêmica, caracterizada pela produção de autoanticorpos, deposição de imunocomplexos, inflamação sistêmica, além de dano tecidual. Cerca de 37% a 45% dos pacientes com LES, desenvolvem nefrite lúpica (NL) em algum momento do curso da doença. Uma proporção de 10 a 30% dos pacientes com NL evoluem para doença renal crônica (DRC), em um prazo de 15 anos após o diagnóstico, mesmo com o tratamento agressivo. Objetivo: Analisar o perfil sociodemográfico, clínico e laboratorial de pacientes com NL submetidos a transplante renal de um hospital público terciário. Detectar a recidiva do LES e o tempo de sobrevidas do enxerto renal e do paciente. Identificar o escore do índice de dano através dos critérios do Systemic Lupus International Collaborating Clinics (SLICC) em pacientes com LES. Comparar a sobrevida renal dos pacientes em estudo com outra pesquisa brasileira com o perfil clínico semelhante. Métodos: Foram analisados todos os registros de pacientes submetidos a transplante renal do período de Julho de 1996 a maio de 2016 no Hospital Geral de Fortaleza (HGF), centro de referência Norte Nordeste em transplantes. Destes, foram selecionados os de pacientes com diagnóstico de NL como causa de DRC terminal (n=35), que preenchiam critérios do Colégio Americano de Reumatologia (ACR). Resultados: De um total de 1.861 transplantes renais, 38 (1.8%) foram realizados em 35 pacientes com NL, 3 dos quais foram submetidos a mais de um transplante. A média de idade dos pacientes no diagnóstico do LES foi de 33,0 ± 11,1 anos. A maioria era do sexo feminino (94,7%) e não-caucasianos (68,4%). 57,9% foram submetidos à biópsia renal antes do transplante. A média do SLICC foi de 4,7 ± 1,2. A maioria dos doadores (71,1%) eram falecidos. A média do tempo do diagnóstico do LES até o transplante renal foi de 10,3 ± 6,4 anos. O tempo médio de diálise prévio ao transplante foi 3,9 ± 3,7 anos. A taxa de rejeição aguda, no primeiro ano, foi identificada em 7,9% dos pacientes. As sobrevidas do enxerto e do paciente foram respectivamente, 97,1% e 100% aos seis meses; 84,9% e 96,9%, no primeiro ano, e 73,3% e 92,5%, no quinto ano. 2,6% apresentou recidiva do LES. Comparando os pacientes que evoluíram com perda do enxerto e os que mantiveram boa função do enxerto, observamos uma maior prevalência de trombose (p=0,017) e síndrome antifosfolípide (p=0,036) no primeiro grupo. Conclusão: O estudo demonstrou que pacientes com NL submetidos a transplante renal apresentam uma boa sobrevida em um período de seguimento de 5 anos e que a presença de trombose e síndrome antifosfolípide foram fatores importantes para a perda do enxerto. Palavras-chave: Transplante de rim; Nefrite lúpica; Lúpus eritematoso sistêmico.